A cross analysis on the use of Malaysian states tourism website in promoting ecotourism destinations - Sumathi Subramaniam, 1980-; Noor Hazarina Hashim, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2010)
Thesis (Sarjana Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2010